The Effectiveness and efficiency of corporate innovation under strict market regulation: Based on China’s new securities law - Zhenna Huang (PLoS ONE, 2025)
The revision of the new securities law (NSL) represents a market-oriented reform of China’s securities market centred on the registration-based system. On the basis of data from all A-share listed companies in China from 2015 to 2022, this study employs the NSL as a quasinatural experiment and uses the difference-in-differences (DID) method to evaluate the impact of NSL implementation on the effectiveness and efficiency of corporate innovation. The empirical results indicate that the implementation of the NSL has a significant positive effect on both the effectiveness and efficiency of corporate innovation. This conclusion remains robust after supplementary tests, such as changing the regression method, replacing the dependent variables, excluding municipalities directly under the central government, and accounting for the impact of the pandemic, are conducted. The mediation effect analysis reveals that NSL implementation significantly affects corporate innovation by alleviating financing constraints, enhancing firms’ risk-taking capacity, and strengthening corporate governance. Furthermore, the moderation effect analysis indicates that the corporate governance environment influences the effectiveness of the NSL on corporate innovation. In a poor corporate governance environment, the benefits of the NSL may not effectively translate into improved corporate innovation outcomes. This study provides important evidence for advancing capital market reforms and improving corporate governance while emphasizing the policy implications of strengthening legal protections to enhance corporate innovation capabilities.